NIR-II fluorescence microscopic bioimaging for intrahepatic angiography and the early detection of Echinococcus multilocularis microlesions - Alifu, Nuernisha; Yan, Ting; Li, Jun; Zhu, Lijun; Aini, Abudusalamu; Amuti, Siyiti; Wu, Juan; Qi, Wenjing; Guo, Gang; Zhang, Wenbao; Zhang, Xueliang (Frontiers in Bioengineering and Biotechnology, 2023)
Hepatic alveolar echinococcosis (HAE) is caused by the metacestode of echinococcus multilocularis, which shows characteristic of malignant tumors with high mortality. However, the traditional diagnostic imaging methods are still not sufficient for the recognition of HAE microlesions in the early stages. Near-infrared II (900-1700 nm, NIR-II) fluorescence microscopic imaging (NIR-II-FMI) has shown great potential for biomedical detection. A novel type of negative targeting imaging method based on NIR-II-FMI with assistance of indocyanine green (ICG) was explored. Then, the NIR-II-FMI was applied to the early detection of HAE for the first time. The negative targeting NIR-II fluorescence imaging of HAE infected mice at different stages with assistance of ICG under 808 nm laser irradiation was obtained. Especially, the HAE microlesions at the early stage were detected clearly. Moreover, clear intrahepatic angiography was achieved under the same NIR-II-FMI system.